Gender difference in the relationship between uric acid and pulse pressure among Korean adults. (18th August 2019) - Park, Chang Eun; Sung, Hyun Ho; Jung, Eun Young; Moon, Ae Eun; Kim, Han Soo; Yoon, Hyun
ABSTRACT: Hyperuricemia is associated with cardiovascular disease, but the relationship between uric acid (UA) and pulse pressure (PP) is unclear. Therefore, the present study assesses the relationship between UA and PP among Korean adults. Data from 6, 310 subjects (2, 800 men and 3, 510 women) in the seventh Korean National Health and Nutrition Examination Survey (2016) were analyzed. After adjusting for related variables, the odds ratios (ORs) of hyperuricemia (UA ≥ 7.0 mg/dL in men or ≥ 6.0 mg/dL in women) in the high PP group (PP > 65.0 mmHg) in overall populations (OR, 1.563; 95% confidence interval [CI], 1.144–2.136) and women (OR, 1.631; 95% CI, 1.046–2.544) were significantly higher than those in normal PP, but not in men (OR, 1.309; 95% CI, 0.840–2.040). In conclusion, uric acid was positively associated with pulse pressure in women, but not in men.